Persepsi Mahasiswa dan Kepatuhan Pembayaran Pajak Kendaraan di Kota Samarinda - Praja Hadi Saputra (Institut Bisnis dan Informatika Kesatuan, 2021)
This study aims to investigate the perception of compliance of individual vehicle taxpayers in paying their vehicle taxes which are influenced by individual internal factors. Internal factors used are the level of tax understanding, perceptions about the tax system and government, the effectiveness of the tax system as well as the ethical perceptions that individuals have. The results of the survey through questionnaires and data analysis from 93 multiple linear regressions indicated that the internal factors that individuals had regarding the perception of vehicle tax tended to affect their compliance with paying vehicle taxes. The results of this study then have practical implications on the availability of evidence for the government to design relevant vehicle tax systems and regulations because it can give rise to the perception of obedient individuals in paying their vehicle taxes. Keywords: tax compliance, tax system, tax regulation, tax ethics, vehicle tax